Men in Caring Occupations - Simpson, R. author. aut Link
VII, 193 p.
Keywords: Exploring how men in service and caring occupations (cabin crew, primary school teachers, nurses and librarians) both 'do' and 'undo' gender as they manage the potential mismatch between gender and occupational identity, this book engages with the key theoretical concepts of identity, visibility and emotions to examine men's experiences.